NFAT and AP1 are Essential for the Expression of a Glioblastoma Multiforme Related IL-13Ra2 Transcript - Anhua Wu; Katya Ericson; Wang Chao; Walter C. Low (Cellular Oncology)
Background: IL-13Ra2 is overexpressed by gliomas but not by normal tissue. However, the molecular basis for IL-13Ra2 overexpression in gliomas is unknown.